Potensi Pengembangan Bawang Putih (Allium Sativum L.) Dataran Rendah Varietas Lokal Sanur - SARWADANA, SANG MADE; ALIT GUNADI, I GUSTI (AGRITROP, 2012)
Garlic (Allium sativum L.) Local Sanur variety is one of garlic varieties which are commonly cultivated in Bali. This variety has not been identified, although it has been known having good agronomical, as well as good morphological characteristics. The aims of this study were to identify Local Sanur variety has good characteristics for cultivated at low land area. This experiment was conducted at Sanur, the eastern region of Denpasar. The seeds were planted on the 5.0 m x 2.5 m garden bed with the plant spacing of 25 cm x 25 cm. There were 15 replications, hence, 15 garden-beds all. Each garden-bed was divided into two parts. The plants on a part side were used as destructive samples, which were required for the variables of growth analysis, and for determination of the period of vegetative and bulbing phase. Whereas the plants on the other part were used for the variables of plant growth and yield. The result show that the variety of Local Sanur had specific characteristics as described below: the plant height ranged 48.9 to 56.7 cm, the leaf number was 5.14 to 6.06; the leaf size were 35.73 to 40.73 cm in length and 1.05 to 1.39 cm in width. The bulbing phase was commenced at 49 days after planting; therefore the vegetative period was 49 days. The bulb was harvested at 85 days after planting, indicated the bulbing period of 36 days. The yield was 4.82 to 6.60 tons of dry weight per hectare. It was also identified that the bulb has oval shape (egglike) with white flesh and yellowish white skin. Those characters indicated that Local Sanur Varierty suitable for developing at low land area.
Keywords: low-land, garlic, Local Sanur variety, and morphological characteristics